AR-V7 and prostate cancer: The watershed for treatment selection?. (February 2016) - Ciccarese, Chiara; Santoni, Matteo; Brunelli, Matteo; Buti, Sebastiano; Modena, Alessandra; Nabissi, Massimo; Artibani, Walter; Martignoni, Guido; Montironi, Rodolfo; Tortora, Giampaolo; Massari, Francesco
Highlights: Prostate cancer is an androgen-dependent tumor, relying on the androgen receptor (AR). Translational research focuses on the identification of biomarkers predictive of treatment response. Recent advances highlighted the role of androgen receptor splice variants (AR-Vs), mainly AR-V7, as potential prognostic and predictive biomarkers. ARv-V7 seems to be a prognostic marker of aggressive cancer behavior, being associated with shorter survival in CRPC patients. AR-V7 seems to be involved in limiting the efficacy of androgen deprivation therapies, in mediating resistance to enzalutamide and abiraterone, and in influencing the prostate cancer sensibility to anti-microtubules chemotherapeutics. Abstract: The androgen receptor (AR) plays a key role in progression to metastatic castration-resistant prostate cancer (mCRPC). Despite the recent progress in targeting persistent AR activity with the next-generation hormonal therapies (abiraterone acetate and enzalutamide), resistance to these agents limits therapeutic efficacy for many patients. Several explanations for response and/or resistance to abiraterone acetate and enzalutamide are emerging, but growing interest is focusing on importance of AR splice variants (AR-Vs) and in particular of AR-V7. Increasing evidences highlight the concept that variant expression could be used as a potential predictive biomarker and a therapeutic target in advanced prostate cancer. Therefore, understanding the mechanisms of treatment resistance or sensitivity can help to achieve a more effective management of mCRPC, increasing clinical outcomes and representing a promising and engaging area of prostate cancer research.